PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN PADA PT FKS FOOD SEJAHTERA TBK PERIODE TAHUN 2014-2023 - Mahalia, Chika; Nurwita, Nurwita (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to examine the effect of liquidity and solvency on company value at PT FKS Food Sejahtera Tbk during the period 2014–2023. Liquidity is proxied by Current Ratio (CR), solvency by Debt to Equity Ratio (DER), and company value by Price Book Value (PBV). This study uses a quantitative approach with multiple linear regression analysis methods, t-test (partial), and F-test (simultaneous) using SPSS ver 25. The results of the study indicate that partially, CR does not have a significant effect on PBV (significance value 0.654 > 0.05; t count 0.468 < t table 2.365), while DER has a significant effect on PBV (significance value 0.032 < 0.05; t count 2.664 > t table 2.365). Simultaneously, CR and DER significantly influence PBV, indicated by the calculated F value of 5.506 > Ftable 4.74 and a significance of 0.037 < 0.05. The coefficient of determination (R²) value of 0.611 indicates that 61.1% of the variation in PBV can be explained by CR and DER, the remaining 38.9% is influenced by other variables. This finding indicates that solvency has a more dominant influence than liquidity in determining company value.